Boosting executive skills in the classroom a practical guide for educators - Cooper-Kahn, Joyce; Foster, Margaret, 1955- (San Francisco : Jossey-Bass, 2013)
"A guide for helping students with weak Executive Function skills to learn efficiently and effectively Students with weak Executive Function skills need strong support and specific strategies to help them learn in an efficient manner, demonstrate what they know, and manage the daily demands of school. This book shows teachers how to do exactly that, while also managing the ebb and flow of their broader classroom needs. From the author of the bestselling parenting book Late, Lost, and Unprepared, comes a compilation of the most practical tools and strategies, designed to be equally useful for children with EF problems as well as all other students in the general education classroom.Rooted in solid research and classroom-tested experience, the book is organized to help teachers negotiate the very fluid challenges they face every day; educators will find strategies that improve their classroom "flow" and reduce the stress of struggling to teach students with EF weaknesses. Includes proven strategies for teachers who must address the needs of students with Executive Function deficits Contains information from noted experts Joyce Cooper-Kahn, a child psychologist and Margaret Foster, an educator and learning specialist Offers ways to extend learning and support strategies beyond the classroom The book's reproducible forms and handouts are available for free download This important book offers teachers specific strategies to help students with EF deficits learn in an efficient manner, demonstrate what they know, and manage the daily demands of school"--
Machine generated contents note: About the AuthorsAcknowledgmentsIntroductionPart One: Executive Functioning: The Basics1 What Is Executive Functioning?DefinitionCore Executive SkillsHow Do Executive Skills Develop?To Sum UpTime to Reflect2 Putting a Face on Executive Functions: Students Who StruggleExecutive Dysfunction: A Description, Not a DiagnosisThe Normal Variability of Executive FunctioningThe Vulnerability of Executive FunctioningPoorly Targeted InstructionThe Importance of Healthy HabitsAssessmentTo Sum UpTime to ReflectPart Two: Interventions That Boost Executive Functions3 The EF-Smart ClassroomThe Tune-up Tools: Planning, Time, Repetition, and Mind-SetThe Targets: Classroom Culture, Planning Instruction, Classroom Routines, and Classroom DesignPlanning for ChangeTo Sum UpTime to Reflect4 Supporting Students Who Need More HelpPlannersMaterialsReadingWritingMathTo Sum UpTime to Reflect5 The EF-Smart School"Old School" to New SchoolsFaculty MeetingsGathering ReferencesThe Magic FormulaTime to ReflectTo Sum Up6 How the Specialist Can HelpExamining the Learning Task and Its EF DemandsExamining Student Executive Skills for Levels of Automaticity and Independence: The Four-Quadrant ModelConsulting with TeachersTime to ReflectTo Sum Up7 Planning for ChangeDefining a Problem of PracticePlanning and Reflection GuideUsing the Template and Guide: Case ExamplesPlan to MonitorTime to ReflectTo Sum UpConclusion: Helping All Students BlossomAppendix A: The Top Three Accommodations for Students with EF ProblemsAppendix B: Accessing the Online MaterialsEndnotesIndex.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Children with mental disabilities -- Education; Executive functions (Neuropsychology); Electronic books